2020
DOI: 10.1155/2020/3050189
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Quality Control: Impurity and Nicotine Level Analysis in Electronic Cigarette Refill Liquids

Abstract: This work targets mainly the quality control of electronic cigarette liquids. It relies on an analytical control of a “32-product” sample made of several types of e-cigarette liquids taken from various supermarkets and tobacconist’s offices in Morocco. All along this study, we made sure to check both the conformity of the nicotine level indicated in the packaging of each product and the existence of any other components inside the product, especially toxic or unknown impurities. The method used for this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The differences between actual and labeled nicotine content have been determined in several studies and presented as percent deviation of actual nicotine concentration from labeled concentration and are summarized in Table 4. The percentages of e-liquids in which the actual quantified nicotine concentrations that deviated by more than ±10% from the manufacturer labels were 10% [24], 18% [15], 52% [12], 56% [25], 63% [26], 65% [27], and 67% [9]. In this study, more than ±10% deviations were detected in 9 out of 11 e-liquids (82%) which are more than what stated in previous similar studies.…”
Section: Nicotine Concentrations In the Most Popular Brands Eliquidssupporting
confidence: 44%
“…The differences between actual and labeled nicotine content have been determined in several studies and presented as percent deviation of actual nicotine concentration from labeled concentration and are summarized in Table 4. The percentages of e-liquids in which the actual quantified nicotine concentrations that deviated by more than ±10% from the manufacturer labels were 10% [24], 18% [15], 52% [12], 56% [25], 63% [26], 65% [27], and 67% [9]. In this study, more than ±10% deviations were detected in 9 out of 11 e-liquids (82%) which are more than what stated in previous similar studies.…”
Section: Nicotine Concentrations In the Most Popular Brands Eliquidssupporting
confidence: 44%
“…There were two occasions where the label indicated that the e‐liquid contained nicotine (3 mg/ml) and when tested it did not, hence the 100% difference between labelled and measured nicotine. This could be due to no nicotine being present or the level of nicotine in the product was below the limit of detection or quantification 48 . In one case, there was a 103.3% difference between the labelled and quantified nicotine; however, this indicated that the quantified nicotine was more than double the labelled nicotine, neither of which were zero.…”
Section: Mislabelling Of E‐cigarettesmentioning
confidence: 94%
“…Therefore, it was determined that a nonparametric test was most appropriate to use here. Two previous studies that compared labelled and experimental nicotine concentrations in e‐liquids used a paired t test 46,48 . As the data in this study are not normally distributed, the nonparametric equivalent of a paired t test was used.…”
Section: Mislabelling Of E‐cigarettesmentioning
confidence: 99%
See 2 more Smart Citations